Barriers and facilitators of micronutrient supplementation among non-pregnant women of reproductive age in Johannesburg, South Africa. - Takana M Silubonde; Catherine E Draper; Jeannine Baumgartner; Lisa J Ware; Cornelius M Smuts; Shane A Norris (Public Library of Science (PLoS), 2022)
The prevalence of anaemia among South African women of reproductive age (WRA) remains high at 39%. Multiple micronutrient supplementation (MMS) may be an effective strategy in the prevention and management of anaemia. Our aim was to understand facilitators and barriers to preconception MMS adherence and to explore perceptions and beliefs of MMS in the prevention and treatment of anaemia among non-pregnant WRA. This qualitative study was embedded in a preconception MMS intervention trial of WRA and was conducted in two phases. Phase one assessed the barriers and facilitators of MMS adherence. Individual interviews were conducted with the community health workers (n = 7) administering MMS, and with non-pregnant WRA (n = 25) participating in the trial. Phase two included four focus groups with participating WRA (n = 26), which further explored participants' perceptions and beliefs of MMS provision and adherence, and strategies to improve adherence. The reported facilitators to supplementation were family support, interaction with the community health workers, easy access to MMS, and experienced benefits of MMS. Barriers to preconception supplementation included the lack of family support, the link of supplements to antenatal care, and the perceived lack of benefits of MMS. Participants reported negative associations of supplements with medication, individual and societal stigma around medication and challenges around the supplementation schedule. For successful preconception MMS interventions, young women, their families, and communities need to be convinced of the value of supplementation. Public health interventions utilising preconception supplementation will require specialised training for health care providers, targeted counselling materials and community household support.